2017
DOI: 10.3400/avd.oa.17-00049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Popliteal-To-Distal Bypass Combined with Femoropopliteal Artery Endovascular Treatment for Critical Limb Ischemia

Abstract: Objective: The aim of this study was to evaluate outcomes of combined popliteal-to-distal bypass and endovascular treatment (EVT) for femoropopliteal lesions in patients with critical limb ischemia (CLI). Patients and Methods: We reviewed data of 14 CLI patients who were treated by popliteal-to-distal bypass combined with femoropopliteal EVT. The femoropopliteal lesions included 3 TASC II-A, 8 TASC II-B, and 3TASC II-C but no TASC II-D, and balloon dilatation was performed in 9 cases and a stent was placed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…With regards to a recent study of femoral popliteal bypass in the symptomatic patients with TASC C and D, the 1-year and 5-year primary patency rate following the bypass surgery were 82.1% and 69.4 %, while these rates were lower in EVT as 67.8% and 45.2%, respectively [6] . Referring to the secondary patency, the 1-year and 5-year rates were 93.2% and 79.5% in femoral popliteal bypass surgery group and 90.1% and 85.1% in EVT group, respectively [7] . Despite the lower primary patency rate in EVT group comparing with bypass surgery, EVT had similar rates with bypass surgery in the secondary patency result.…”
Section: Discussionmentioning
confidence: 95%
“…With regards to a recent study of femoral popliteal bypass in the symptomatic patients with TASC C and D, the 1-year and 5-year primary patency rate following the bypass surgery were 82.1% and 69.4 %, while these rates were lower in EVT as 67.8% and 45.2%, respectively [6] . Referring to the secondary patency, the 1-year and 5-year rates were 93.2% and 79.5% in femoral popliteal bypass surgery group and 90.1% and 85.1% in EVT group, respectively [7] . Despite the lower primary patency rate in EVT group comparing with bypass surgery, EVT had similar rates with bypass surgery in the secondary patency result.…”
Section: Discussionmentioning
confidence: 95%
“…Many investigators have reported combining SFA EVT with popliteal-to-distal bypass; however, only a few recent detailed reports exist. [10][11][12][13] Schanzer et al 10 reported in their series of 23 combined procedures, that the secondary patency of distal bypass graft was 69% at 3 years. Marcucci et al 12 reported in their series of 23 combined procedures that the secondary patency was 82% at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…9 A few recent reports of the combined procedure with conventional techniques such as plain old balloon angioplasty (POBA) or self-expandable nitinol stent exist, but these reports do not include SFA EVT with a "contemporary device" such as stent graft, drugcoated balloon, drug-eluting stent, and interwoven nitinol stent. [10][11][12][13] The purpose of this study was to evaluate the results of combining SFA EVT, primarily using a "contemporary device," with distal bypass graft originating from the popliteal artery, and to discuss a paradigm shift in surgical open bypass for CLTI.…”
Section: Introductionmentioning
confidence: 99%